Analisis Eksternalitas Positif “Wisata Alam 21” - Wahyudi, Heru; Ardianto, Eko (Jurnal Studi Perhotelan dan Pariwisata, 2022)
Purpose: This study aims to analyze differences in economic and social conditions of the community before and after the existence of Nature Tourism 21 in Aji Mesir Village, Gedung Aji District, Tulang Bawang Regency. The aspects in this study are aspects of economic conditions and social conditions. Research methodology: The research method used in this study uses a descriptive-comparative method with a qualitative approach. The data analysis method in this study used a different test analysis with the Wilcoxon Signed Rank Test. Results: The results showed that there were significant differences between economic conditions, and social conditions, before and after the existence of Nature Tourism 21 which was felt by the community of Aji Mesir Village, Gedung Aji District, Tulang Bawang Regency. Limitations: The limitation of this study is only to analyze the positive externalities and not to analyze the negative externalities of “Wisata Alam 21”. Contribution: The results obtained from this study are expected to be one of the references in making policies based on the data presented to adjust the right policies, especially to increase the positive externalities of “Wisata Alam 21”.